Formulation and Antioxidant Activity Test of Hand Cream Extzract of Kumis Kucing Leaf (Orthosiphon Stamineus) Using DPPH (2,2- Diphenyl-1-Picrylhydrazyl) Methods - Indah Zahara; Vani Aprilia Lestari; Adelia Putri; Sherly Novitasari; Nabila Octavianti (Riviera Publishing, 2026)
Extract of kumis kucing leaves (Orthosiphon stamineus) contains secondary metabolites, namely flavonoids, tannins, saponins, and phenolics. This study conducted an antioxidant activity test on the extract and its formulations. The aim of this research is to determine the antioxidant activity of the kumis kucing leaf extract and formulations, and to formulate it into a hand cream preparation at concentrations of 5 g, 10 g, and 15 g. The antioxidant activity of the extract and formulations was measured using UV-Vis spectrophotometry. The results of this study show that the IC50 value of the kumis kucing leaf extract (Orthosiphon stamineus) is 74 ppm. For the formulations, the IC?? values are as follows: Formulation 0 has an IC50 value of 257 ppm, Formulation 1 has an IC50 value of 108 ppm, Formulation 2 has an IC50 value of 91 ppm, and Formulation 3 has an IC50 value of 84 ppm. The hand cream preparations present as white, green, dark green, and dark greenish-black in colour respectively, with a characteristic scent of kumis kucing leaves, in cream form, with a pH range of 5–7, a spreadability range of 5–7 cm, an adhesion range of 4–8 seconds, and a viscosity range of 4,000–36,000 cps. The results confirm antioxidant activity in both the kumis kucing leaf extract and the formulations. The best formulation was Formulation 3, with an IC50 value of 84 ppm, while Formulations 1, 2, and 3 all meet the requirements for a good cosmetic preparation.